ANALISIS PENGARUH RADIUS FILLET TERHADAP KONSENTRASI TEGANGAN PADA POROS TRANSMISI BAJA AISI 1040 - Firman Alhaffis; Erwen Martianis; Maksum; Ahmad Aidil Rasyid; Rusmanidar (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Shafts are crucial components in mechanical transmission systems that transfer power between moving machine elements. In high-speed applications, shafts experience dynamic and cyclic loads that can trigger material failure due to fatigue, especially in cross-sectional areas such as stepped shafts. Stress concentrations that occur in diameter transition areas can be the starting point for cracking that leads to structural failure. One method to reduce these stress concentrations is by applying a fillet radius to the diameter change area. This study aims to analyze the effect of fillet radius on torsional and bending loads on a transmission shaft made of AISI 1040 steel. The method used is a numerical simulation based on Finite Element Analysis (FEA). It was found that the application of an 11 mm fillet radius on the stepped shaft provided better performance compared to a 1 mm fillet radius for a diameter transition from 190 mm to 150 mm. The use of an 11 mm fillet radius on the stepped shaft made of AISI 1040 material resulted in a decrease of total deformation by 1.8%, equivalent elastic strain by 4.24%, and, most notably, equivalent elastic stress by 75%.